Readiness of Early Childhood Learning at Integrated Raudhatul Athfal Islam Insan Kamil during the Covid 19 Pandemic - Aprilliana Purwaningtyas; Ghozali Rusyid Affandi (Indonesian Journal of Islamic Studies, 2021)
The research method used is descriptive quantitative type which was carried out at Raudhatul Athfal Islam Terpadu Insan Kamil, Sidoarjo. The population in this study were 75 children using purposive sampling. This study used the NST test. The results of this study indicate that children's learning readiness during online learning at Raudhatul Athfal Islam Terpadu Insan Kamil, Sidoarjo indicates that children's online learning readiness is 29% ready, 32% quite ready, and 39% not ready. The comparison of male students' learning readiness is 43.14% greater than female students' which is only 41.86%. The highest aspect comparison among the 10 aspects, the highest is aspect 1 with an average score of 5.17 and the lowest is in the fifth aspect with a value of 3.96. Comparison of each aspect in terms of gender, male has the highest score in aspect 1 with an average score of 5.43 which is higher than female with a score of 4.64. Meanwhile, the highest score for women is in the eighth aspect with a score of 4.43 which is higher than that of men, which is only 4.14. Overall, it can be concluded that online learning has an effect on learning readiness at Raudhatul Athfal Islam Terpadu Insan Kamil, Sidoarjo with the result of poor learning readiness. The results of this study recommend to schools to provide parenting and to parents to supervise the children's learning process while online.